Quality dimensions in online communities influence purchase intentions. Issue 9 (16th October 2017) - Wang, Chung-Yu; Lee, Hsiao-Ching; Wu, Li-Wei; Liu, Chih-Chung
Abstract : Purpose: The purpose of this paper is to examine how quality dimensions in independently owned online brand communities influence purchase intentions via uncertainty reduction and the role of involvement. Design/methodology/approach: This work validates the model and hypotheses through non-probabilistic sampling. The online questionnaire was made on the website of MySurvey and an invitation letter was posted to the forums. The respondents received the questionnaire items translated into Chinese. The final survey sample consisted of 235 respondents. Findings: Empirical results confirm that as for independently owned online brand communities, their information quality and relationship quality are effective tools for influencing purchase intentions via uncertainty reduction. In addition, the authors demonstrate that involvement has a positively moderating influence on the relationship between uncertainty reduction and purchase intentions. Originality/value: The current study moves beyond uncertainty reduction to demonstrate that information quality and relationship quality of forums influenced purchase intention via uncertainty reduction and the moderating variable such as involvement.